Impact of in situ NH3 pre-treatment of LPCVD SiN passivation on GaN HEMT performance. (25th January 2022) - Chen, Ding-Yuan; Persson, Axel R; Wen, Kai-Hsin; Sommer, Daniel; Grünenpütt, Jan; Blanck, Hervé; Thorsell, Mattias; Kordina, Olof; Darakchieva, Vanya; Persson, Per O Å; Chen, Jr-Tai; Rorsman, Niklas
Abstract: The impact on the performance of GaN high electron mobility transistors (HEMTs) of in situ ammonia (NH3 ) pre-treatment prior to the deposition of silicon nitride (SiN) passivation with low-pressure chemical vapor deposition (LPCVD ) is investigated. Three different NH3 pre-treatment durations (0, 3, and 10 min) were compared in terms of interface properties and device performance. A reduction of oxygen (O) at the interface between SiN and epi-structure is detected by scanning transmission electron microscopy (STEM )-electron energy loss spectroscopy (EELS) measurements in the sample subjected to 10 min of pre-treatment. The samples subjected to NH3 pre-treatment show a reduced surface-related current dispersion of 9% (compared to 16% for the untreated sample), which is attributed to the reduction of O at the SiN/epi interface. Furthermore, NH3 pre-treatment for 10 min significantly improves the current dispersion uniformity from 14.5% to 1.9%. The reduced trapping effects result in a high output power of 3.4 W mm −1 at 3 GHz (compared to 2.6 W mm −1 for the untreated sample). These results demonstrate that the in situ NH3 pre-treatment before LPCVD of SiN passivation is critical and can effectively improves the large-signal microwave performance of GaN HEMTs.